Combining CEFR and 4C CLIL Frameworks for Principled Literature in Language Teaching - Redlich, Jeremy; Pattison, Steven (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
An abundance of research and scholarship highlighting why and how literature (i.e., novels, plays, poetry, short stories) can be used effectively in foreign language learning contexts exists. However, these publications tend to prioritize “literary” learning objectives over “language” learning objectives. We aim to support the effective teaching of literature in foreign language learning classrooms by providing a structured and principled approach to developing an integrated literature in language learning course or module that equally prioritizes “content” and “language” learning objectives. By adopting the 4C (Content, Cognition, Culture, and Communication) framework from CLIL, and by adapting CEFR principles, benchmarks, and Can-do statements, we propose a method and framework for developing the beginning-to-end stages in a balanced literature in language learning course design. We outline pedagogically sound steps for creating global learning objectives and activities that engage students of varying motivations and language proficiency levels. The organization of CEFR Can-do statements into the 4C framework is presented. In addition, activities for use in a literature classroom are described, including explanations of the underlying Can-do statements and aspects of the 4C framework they support. The proposed method and framework will aid instructors seeking to utilize literary texts in foreign language learning contexts.